Projeto e execução de lajes unidirecionais com vigotas em concreto armado - Flório, Márcio Cardozo (Universidade Federal de São Carlos, 2003)
This work presents design and executive procedures for pre-cast slabs with unidirectional ribs, which are one of the most used construction elements for small buildings in the country, discussing aspects related to constructive details and both to limit state and service limit design procedures. Many construction details are discussed, such as choice of adequate concrete strength, placement, consolidation and cure of concrete, materials quality assurance tests, formwork, minimum distance between supports to different kinds of joists, camber details and others. Regarding the design procedure, there is study about the consideration of cracking and creep in the deflections service state design and also about shear and flexure reinforcement limit state design. Considerations related to panel continuity and walls directly supported by the slab were taken into account. Special care was taken during the work in other to try to suit design theories to construction techniques already known and used in large scale. Recommendations included in the new concrete code NBR 6118 (2003) were also analyzed. The tests presented were performed mainly by Grupo de Estudos de Sistemas Estruturais em Concreto da UFSCar in which the author belongs in, including a series of tests to measure deflections in pre-cast slab taking in account the creep and cracking phenomena.
Design and construction of concrete pre-cast slabs with unidirectional ribs
Keywords: Construção civil; Lajes de concreto; Concreto armado; Concreto pré-moldado; Fissuração; Fluência; Slab; Reinforced concrete; Joist; Pre-cast; Cracking; Creep; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL